Mesozooplankton and Micronekton Active Carbon Transport in Contrasting Eddies - Kwong, Lian E.; Henschke, Natasha; Pakhomov, Evgeny A.; Everett, Jason D.; Suthers, Iain M. (Frontiers in Marine Science, 2020)
Mesozooplankton (June 2015 and September 2017) and micronekton (September 2017) were sampled along the eastern coast of Australia. Depth stratified mesozooplankton and micronekton were collected using a Multiple Opening/Closing Net and Environmental Sensing System (MOCNESS) and an International Young Gadoid Pelagic Trawl (IYGPT) equipped with an opening/closing codend. Sampling was undertaken at the center and edge of a frontal cold-core eddy (F-CCE center and edge) in 2015, and at the center of a cold-core eddy (B-CCE) and two warm-core eddies (R-WCE and WCE) in 2017. We assess the diel vertical structure, biomass and downward active carbon transport by mesozooplankton and micronekton in eddies. Total water column mesozooplankton and micronekton biomass did not vary substantially across water masses, while the extent and depth of diel vertical migration did. Using in-situ measurements of temperature and measurements of mesozooplankton and micronekton abundance and biomass, we estimated the contribution of respiration, dissolved organic carbon (DOC) excretion, gut flux and mortality to total downward active carbon transport in each water mass. Overall, active carbon transport by mesozooplankton and micronekton below the mixed layer varied substantially across water masses. We corrected estimates of micronekton migratory biomass and active carbon transport assuming 50% net efficiency. Specifically, inIn the R-WCE mesozooplankton remained within the mixed layer during the day and night; only 50% of the total micronekton population migrated below the mixed layer contributing to carbon transport, equating to 1.52.89 mg C m-2 d-1. Mesozooplankton actively transported 16.1 and 8.0 mg C m-2 d-1 at the F-CCE Center and Edge, respectively. Mesozooplankton and micronekton active carbon transport in the B-CCE were 5.4 and 0.40.74 mg C m-2 d-1, and in the WCE 88 and 6.713.4 mg C m-2 d-1. Differences in carbon export were dependent on food availability, temperature, time spent migrating and mixed layer depth. These findings suggest that under certain conditions mesoscale eddies can act as important carbon sinks.